Altas habilidades ou superdotação e o TDAH: avaliação multidimensional para identificação de indicadores de dupla excepcionalidade - Pereira, Josilene Domingues Santos (2021)
The twice exceptionality (2e) consists, in studies in the area of high abilities or giftedness (AHSD), in the coexistence of AHSD with a disability or disorder or syndrome and has been considered a condition that characterizes a special population of people with AHSD. In this investigation, it was studied the type of 2e is the coexistence of AHSD and Attention Deficit/Hyperactivity Disorder (ADHD). The identification of students with 2e has been identified in the literature as a complex task, due to the fact that both the AHSD characteristics can be masked by the deficiency or disorder or syndrome and these ones can mask the AHSD behaviors. Furthermore, several scholars on this topic have stated that many students with AHSD have been incorrectly diagnosed with ADHD and that many cases of 2e have not even been considered. In this sense, the main objective of this investigation was to propose a multidimensional assessment model (school, family and student) for the identification of indicators of double exceptionality in students, in the school context, who have been diagnosed with ADHD or who have been evaluated with AHSD or showing signs of ADHD. A qualitative, descriptive and exploratory research was carried out through the design of multiple case studies. Nine participants were selected for convenience (three students, three family members and three teachers). The students (cases 1, 2 and 3) were indicated by two schools (public and private) from a medium-sized municipality in the interior of Bahia, Brazil. Instruments (questionnaires, checklists, tests, scales), techniques (semi-structured interview and classroom observation) and documents (school reports) were used for data collection. The results indicated that: i. The evaluation showed that differentiating between AHSD and ADHD is a complex task, due to the similarities between the two conditions; ii. The three cases showed traits indicative of the coexistence of AHSD with ADHD; iii. There were convergences of 2e among the three cases in the following aspects: impairment in executive functions, marked asynchrony, high cognitive capacity, inconsistent pattern in performance, curiosity, ease and speed to learn; high risk of developing the underachievement condition in higher grades, emotional adjustment problems, relationship difficulties in interacting with classmates, interest in space content and social studies, science fiction, scientific projects and experiments; iv. It was observed that the indicatives of involvement with the task were not frequent, which may indicate the non-identification of AHSD by the school and the trait of AHSD behavior harmed by ADHD; v. The lack of training in the area of AHSD of school professionals are barriers to the identification of 2e students and their educational needs. It is possible to conclude that, in all three cases, the students need attention in the disable areas and enrichment of their interests to develop their potential. It is also essential that the assessment for the identification of 2e indicators considers several informants and also multiple instruments, in addition to observations at school and interviews.